A Novel Anti-EGFR mAb Ame55 with Lower Toxicity and Better Efficacy than Cetuximab When Combined with Irinotecan - Zheng, Yiqiong; Yu, Yunzhou; Long, Feng; Pang, Xiaobin; Sun, Zhiwei; Ma, Jinling; Du, Peng; Zeng, Dadi; Wang, Qiong; Yu, Xiaoyan; Wang, Shuang; Zhang, Chang; et al. (Journal of immunology research, 2019)
To improve efficacy and minimize toxicity of EGFR inhibition treatment, we developed Ame55, a novel anti-EGFR IgG1 with lower affinity to EGFR than cetuximab (C225) from a human phage library. Ame55 had lower bioactivity than cetuximab in vitro but similar antitumor efficacy as cetuximab in vivo. Moreover, Ame55 was more efficacious than cetuximab in a Lovo cell xenograft tumor model when combined with irinotecan (CPT-11). Ame55 concentrates in the mouse xenograft tumor and has less toxicity than cetuximab in cynomolgus monkeys in an overdose study.